Role of technology in food waste: A state of the art science mapping on past and future trends - N. H., Zainal Abidin; Muhammad Ashraf, Fauzi; Suziyana, Mat Dahan; Wider, Walton; A. S., Sadun; Ting, Irene Wei Kiong; Fadzida, Ismail (Penerbit Universiti Putra Malaysia, 2024)
The present review evaluated the knowledge structure of food waste reduction behaviour through digital technology. As climate change has become a monumental topic in sustainability development, intervention in human consumption, including food wastage, has become crucial. Through a bibliometric analysis, the present review adopted bibliographic coupling and co-word analysis to reveal the current, emerging, and future trends in food waste behaviour. Past themes related to challenges of food waste management, technological approach in food waste management, and determinants of food waste behaviour among consumers. Future trends related to lifecycle management of food waste technologies and food waste in municipal solid waste management. The findings of the present review would be beneficial to researchers and practitioners of food waste management in reducing the impact of food waste among consumers. The present review also corroborated the crucial role of technology in food waste reduction management.